Extramedullary plasmacytoma in the penile bulb of a dog: Case report - Gorenstein, T. G. [UNESP]; Jark, P. C. [UNESP]; Feliciano, M. A R [UNESP]; Sueiro, F. A R [UNESP]; Anai, L. A. [UNESP]; Fenerich, M. [UNESP]; Senhorello, I. L S [UNESP]; Rodrigues, B. C. [UNESP]; Tinucci-Costa, M. [UNESP] (FapUNIFESP (SciELO), 2016)
Non-cutaneous extramedullary plasmacytomas are relatively rare in dogs, affecting mainly the oral cavity and bowel loops. The involvement of the penile bulb has not been described, a fact of great importance for obstetric and veterinary oncology. The aim of this case report is to describe the occurrence of plasmacytoma in a dog's penile bulb, classified as a non-cutaneous extramedullary disease of rare location and unpublished casuistry. A non castrated dog of undefined breed, with seven years of age and weighing 15kg, presented clinical history of anorexia, vomiting, anuria and constipation. By specific examination of the external genitalia, a penile bulb mass was found in the preputial inspection, which was adhered to the encapsulated skin, extremely firm and rounded, measuring approximately 6 cm in diameter. By ultrasound evaluation of the structure in the penile bulb an increase of regional volume with heterogeneous echotexture and mixed echogenicity and tissue neovascularization upon color Doppler was observed. Incisional biopsy of the mass was performed and showed the presence of neoplasia of round cells. The characterization of the tumor was performed by immunohistochemistry and the neoplastic immuno cells were expressed CD79a and MUM1, indicating the diagnosis of extramedullary plasmacytoma. Although the penile tumors in dogs are predominantly transmissible venereal tumors (TVT) and plasmocytomas are rare neoplasms in this location, this case report provides a novel occurrence of extramedullary plasmacytoma in the penile bulb of a dog, a condition not yet described in veterinary.
Keywords: Canine; Plasmacytoma; Reproductive system